The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/mmr.2018.9771
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate ameliorates carbon monoxide‑induced cerebral injury in male rats

Abstract: Carbon monoxide (CO) has been shown to induce several cardiovascular abnormalities, as well as necrosis, apoptosis and oxidative stress in the brain. Magnesium sulfate (MS) has been shown to have beneficial activities against hypoxia in the brain. In the present study, the possible protective effects of MS against CO-induced cerebral ischemia were investigated. For this purpose, 25 male Wistar rats were exposed to 3,000 ppm CO for 1 h. The animals were divided into 5 groups (n=5 in each group) as follows: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…The BAX/Bcl-2 ratio is considered a measure of cell susceptibility to apoptosis [28] as well as proapoptotic index [29]. This ratio was found to be significantly decreased in the current study as reported earlier and may be due to the increased apoptosis via increasing proapoptotic Bax and decreasing antiapoptotic Bcl-2 expression in an animal model [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…The BAX/Bcl-2 ratio is considered a measure of cell susceptibility to apoptosis [28] as well as proapoptotic index [29]. This ratio was found to be significantly decreased in the current study as reported earlier and may be due to the increased apoptosis via increasing proapoptotic Bax and decreasing antiapoptotic Bcl-2 expression in an animal model [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…COP leads to inhibition of O 2 transport and development of tissue hypoxia, which in turn causes cell apoptosis 49 . Due to the nonrenewability of neurons, some scholars believe that apoptosis is an important pathogenesis of brain injury caused by COP 23,50 . Jurič et al found that carbon monoxide decreased the activity of astrocyte cells, increased the reactive oxygen species, and reduced the mitochondrial membrane potential and intracellular ATP level.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, vascular dementia is the second most common form of dementia accompanied by obvious cognitive dysfunction after Alzheimer's disease ( 29 ), and MID is a common type of vascular dementia. Currently, no licensed drugs are available for the treatment of vascular dementia ( 30 ), and the reported therapeutic strategies for the disease primarily focus on inhibiting oxidative stress, apoptosis and inflammation ( 31 , 32 ). Multiple and cortical microinfarctions are closely related to dementia and cognition ( 33 ), which is associated with their direct influence on the production of ATP in the brain ( 7 ).…”
Section: Discussionmentioning
confidence: 99%